Effective Rates of Assistance for Norwegian Industries - Erling Holmøy; Torbjørn Hægeland; Øystein Olsen (Statistics Norway, Research Department, 1994)
We measure the effective assistance to 18 Norwegian private industries in 1989 caused by government budgetary subsidies, indirect commodity taxes, import protection through nominal tariffs and non-tariff-barriers, price discrimination of electricity and capital income taxation. The assistance effects are measured by the change in the net-of-tax value added price. Most industries were effectively assisted, but the effective assistance differs widely between industries indicating the overall distortive effect on the industry structure. Agriculture, Fishery and Building of Ships and Oil Platforms stand out as the most assisted industries. Budgetary subsidies and non-tariff barriers had the strongest effective assistance effect.
Keywords: F13; H25; L60; L71; 330; Effective Rates of Assistance; Industrial policy